"Screaming isolation" when is a chair more than a chair? Photographic encounters, IPA and capturing out of awareness experiencing: A novel approach to working with temporal, spatial and embodied dimensions. Issue 4 (2nd October 2022) - Morrey, Tara; Larkin, Michael; Rolfe, Alison
ABSTRACT: This paper focuses on the concept and analysis of photographic encounters which we utilised in an interview study to explore experiences of psychotherapy environments. Our study involves a dual perspective design (a sample of therapists, and a sample of clients). Interviews incorporating photographic encounters were transcribed, and then analysed with Interpretative Phenomenological Analysis. Nine therapists and five clients were recruited from a voluntary counselling service in the West Midlands. Two of the therapists first took photographs of the setting. These photographs were used in the study. Interviews involved participants viewing the photographs and then choosing images to discuss. A theoretical framework for analysing the photographic encounters was incorporated alongside IPA analysis. We show how photographic encounters facilitated insights about how participants were experiencing new, layered and embodied engagement with the therapy environment. We argue that photographic encounters in qualitative interviews can foster awareness of tacit experiencing, and that IPA is an effective and complementary approach for working with such data. Our use of photographic encounters contributes to the existing literature on generating multi-modal accounts of experience using visual methods. This paper also offers a distinctive, conceptually-based framework for use alongside IPA to analyse photographic encounters.